A Diagnostic and Therapeutic Hydrogel to Promote Vascularization via Blood Sugar Reduction for Wound Healing. (15th January 2023) - Han, Xiaoyu; Chen, Shuyu; Cai, Zhengwei; Zhu, Ying; Yi, Weiwei; Guan, Mengtong; Liao, Bo; Zhang, Ying; Shen, Jieliang; Cui, Wenguo; Bai, Dingqun
Abstract: Chronic hyperglycemic damage is a major problem that undermines diabetic wound healing. By combining treatment and diagnosis together, blood glucose concentration can be monitored real‐time through medical imaging devices and precise interventions can be carried out at the right time to promote diabetic wound repair. In this study, an injectable self‐healing hyaluronic acid hydrogel is constructed using Schiff base reaction, and nanoenzymes (GOx‐MnO2 ) synthesized by condensation reaction, along with vascular endothelial growth factor (VEGF)‐nanobubbles produced by double emulsification method, are loaded into the hydrogel, thus constructing an innovative diagnostic and therapeutic hydrogel system (US@GOx@VEGF hydrogel, UGV hydrogel). While monitoring glucose concentration in real‐time, the system delivers VEGF through ultrasound in a precise and noninvasive way to deplete glucose. The UGV hydrogel integrates both processes of diagnosis and treatment, effectively releases VEGF through blasts triggered by ultrasound. Apart from this, this new trauma patch is capable of monitoring Mn 2+ values ranging from 0.5 m to 7.8 × 10 −3 m and glucose levels from 100 × 10 −3 to 3 × 10 −3 m, through magnetic resonance imaging. In summary, the hydrogel realizes real‐time monitoring of glucose level, maintains glucose homeostasis through noninvasive intervention, and rapidly promotes the repair of diabetic skin defects, opening up a new path for chronic wound management. Abstract : Nanoenzymes synthesized by condensation reaction, along with vascular endothelial growth factor (VEGF)‐nanobubbles produced by double emulsification method, are loaded into the injectable self‐healing hyaluronic acid hydrogel, thus constructing an innovative diagnostic and therapeutic hydrogel system. While monitoring glucose concentration in real‐time, the system delivers VEGF through ultrasound in a precise and noninvasive way to deplete glucose.